Treatment of Textile Wastewater Using Nanofiltration - Cebeci, M. Sarioglu; Torun, T. (European Scientific Journal, ESJ, 2017)
The discharge of the synthetic dyes in textile industries is considered to be a major environmental problem due to aesthetically undesirable in receiving waters. Therefore, treatment processes for removing of dyes from textile effluents have become important. Nowadays, removal of dyes is carried out generally by physical and chemical methods. In this study, synthetic textile wastewater was prepared using cationic dye (Methylene Blue) and with addition of other chemicals. The treatment of textile wastewater in the cross flow membrane system was investigated. Flat sheet polymer type nanofiltration membrane (NF) at constant working pressure was used to remove COD (chemical oxygen demand), color, turbidity and conductivity from effluents. Removal efficiencies of COD, color, turbidity, conductivity of samples at 15 bar were found to be 98%, 98%, 100%, and 95%, respectively. Membrane processes can be used to treat textile wastewater and reuse of treated wastewater in the process as process water can be achieved as advanced treatment.